Needs Analysis of Teacher Professional Development to Improve Competence - Karsiwan, Wawan; Komariah, Aan; Satori, Djam’an; Nurdin, Diding (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to explore the needs analysis function in the implementation of teacher professional development programs so that teacher competence can be increased. Analysis was carried out on organizational, task, and career needs. The research method used was mixmethod with Self-Report Inventory instruments, interview guidelines, observation instruments, and guidelines for focus group discussions in Avicenna Junior High School by involving research samples, namely: the human resources department, principals and teachers. The results showed that the development program carried out so far was not maximally based on real needs in answering the problems of teachers in learning. This is indicated by the competency gap by a mean of 0.78. The effectiveness of teacher professional development programs is largely determined by the initial process of analyzing the development needs of teachers in solving learning problems in class. Therefore, in implementing a teacher’s professional development program the first step that must be taken is to conduct a development needs analysis, specifically based on the needs of teachers.